Pengaruh Penggunaan Transtibial Prosthesis dan Axilla Crutch terhadap Tingkat Kepercayaan Diri - fathi, muhammad (Politeknik Kementerian Kesehatan Banjarmasin, 2025)
Background: Loss of limbs due to amputation can cause physical limitations for an individual to carry out activities in daily life. This limitation reduces the level of independence of an individual. The decreased level of independence has an impact on the level of self-confidence due to obstacles in carrying out an activity or goal. Efforts that can be made to increase the self-confidence of transtibial amputation patients are by installing a transtibial prosthesis or axilla crutch which can help mobility. The purpose of this study was to determine the difference in the effect of using a transtibial prosthesis and axilla crutch on the level of self-confidence. Method: This study was conducted in December 2023 with a descriptive qualitative approach using data analysis, namely data reduction, data presentation and drawing conclusions. Results: The results of observations and interviews using self-confidence indicators, namely believing in one's own abilities, being able to do activities without the help of others, having a positive self-concept and daring to express feelings that are felt, which were carried out on two informants, showed that the presence of this transtibial prosthesis was able to foster a new spirit to carry out activities as before. Conclusion: From this study it can be concluded that there is a better effect of using a transtibial prosthesis compared to an axillary crutch.